Training-needs assessment and action - Rao, D. Rama; Soam, S.K.; Sastry, R. Kalpana (2002)
The paper describes the outcome of a major HRD initiative by ICAR. The study is culmination of the training needs assessment by soliciting employees' opinions through a survey questionnaire, brainstormic on key issues and discussions with senior officers and standard training needs manuals. The study identified norms for training expenditure, mandatory training of all new recruits, creation of core faculty for training of administrative and finance staff, Infrastructure to use the gains particularly in information technology, ethics and morals through yoga and meditation and finally training audit. - Reproduced.
Keywords: Training